Automated Solid Phase Extraction of Cd(II), Co(II), Cu(II) and Pb(II) Coupled with Flame Atomic Absorption Spectrometry Utilizing a New Sol-Gel Functionalized Silica Sorbent - Natalia Manousi; Abuzar Kabir; Kenneth G. Furton; George A. Zachariadis; Aristidis Anthemidis (Separations, 2021)
In this study a simple and sensitive on-line sorbent extraction platform coupled with flame atomic absorption spectrometry for trace metals determination was developed. The system utilized for the first time a novel sol-gel thiocyanatopropyl functionalized silica as adsorbent for metal’s separation and preconcentration. The main factors affecting the performance of the on-line system were investigated and optimized. The effect of potential interfering species that occur naturally in environmental and biological samples, as well as some toxic elements, was evaluated. Under optimum conditions the enhancement factors ranged between 73 and 152 for the target analytes. The LODs of the proposed methods were 0.15 μg L−1 for Cd(II), 0.5 μg L−1 for Co(II), 0.5 μg L−1 for Cu(II) and 1.9 μg L−1 for Pb(II) for 120 s preconcentration time. The relative standard deviation values for all elements were less than 3.8%, indicating good method precision. Moreover, the sol-gel thiocyanatopropyl functionalized silica-packed microcolumns exhibited limited flow resistance and excellent packing reproducibility. Finally, the proposed method was utilized for the analysis of environmental and biological samples.